2012
DOI: 10.1093/jrr/rrs041
|View full text |Cite
|
Sign up to set email alerts
|

Interfractional and intrafractional errors assessed by daily cone-beam computed tomography in nasopharyngeal carcinoma treated with intensity-modulated radiation therapy: a prospective study

Abstract: This prospective study was to assess interfractional and intrafractional errors and to estimate appropriate margins for planning target volume (PTV) by using daily cone-beam computed tomography (CBCT) guidance in nasopharyngeal carcinoma (NPC). Daily pretreatment and post-treatment CBCT scans were acquired separately after initial patient setup and after the completion of each treatment fraction in 10 patients treated with IMRT. Online corrections were made before treatment if any translational setup error was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Nonetheless, a prior study that employs post-treatment cone-beam CTs has shown a small intrafraction motion of 1.2 mm during RT delivery to NPC with standard thermoplastic mask immobilization. 33 Our study also lacks treatment toxicity data that would further determine the causes of weight loss. The retrospective nature of this analysis poses the risks of patient selection bias and uncontrolled confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a prior study that employs post-treatment cone-beam CTs has shown a small intrafraction motion of 1.2 mm during RT delivery to NPC with standard thermoplastic mask immobilization. 33 Our study also lacks treatment toxicity data that would further determine the causes of weight loss. The retrospective nature of this analysis poses the risks of patient selection bias and uncontrolled confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study is that it does not account for residual errors because a second (verification) CBCT scan after the repositioning was not carried out. In other studies, for prostate bed [ 11 ] and head and neck [ 23 ] the residual errors were determined by performing a second CBCT after the treatment and matching it with the planning CT. Of course this procedure will also lead to a higher dose exposure to the patient. The assessment of the residual errors will allow to calculate CTV-to-PTV expansion margins when image guidance is used which should in general be smaller than the values obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up from this study also showed that the incidence of post-treatment gastrostomy dependence and oesophageal stricture was lower with reduced margins. 44 These results are reflected in a number of other dosimetric studies which have found that without daily IGRT, PTV margins need to be larger to account for set-up errors [45][46][47][48][49][50] and that the improved setup accuracy with IGRT can potentially lead to improved sparing of normal tissue structures. 51 Frequent volumetric imaging also allows for the detection of soft tissue changes during treatment.…”
Section: Igrt For Head and Neck Cancersmentioning
confidence: 99%